Terpenoid Compounds of Lime (Citrus Aurantifolia) Peel by Using Gas Chromatography Mass Spectrometry (GCMS) Method - mirnawati mirna (Hasanuddin University, 2022)
Terpenoid compounds known as essential oils can be used as flavour enhancers and medicinal sources. The Citrus genus is a citrus aurantifolia species. Citrus aurantifolia (Rutaceae) is a fruit type most often consumed by the public. This study aimed to determine the terpenoid compounds contained in lime peel extract (C. aurantifolia). This study used the extraction method for 3 x 24 hours and then continued by using a sonicator. The viscous extract was then analyzed by using a GCMS method. This study obtained that the β-pinene compound for the retention time was 7.92, and the per cent area was 34.81 %. While for the D-limonene compound for the retention time was 6.62, and the per cent area was 20.15 %